2019
DOI: 10.3892/etm.2019.7739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid diseases on pregnancy outcomes

Abstract: The current study aimed to analyze the effects of thyroid diseases on pregnancy outcomes and investigate the effects of levothyroxine (L-T4) tablets in the treatment of hypothyroidism. The current study determined the prevalence of thyroid diseases using two diagnostic criteria, the prevalence of thyroid diseases among pregnant women recruited in 2010 and 2014 were initially determined by the 2011 Guidelines of the American Thyroid Association for the Diagnosis and Management of Thyroid Disease During Pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 43 publications
(50 reference statements)
0
29
0
7
Order By: Relevance
“…Observing also that higher TAI titers increased as age in the RPL group in the range of 31 to 35 years, after which a decrease in frequency was observed. Two other meta-analyses also reported [9,10] that the mean age with positive TAI in women with RPL was slightly higher than women with negative TAI. In this study, there was no statistically significant difference in the mean age in women with positive and negative TAI.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Observing also that higher TAI titers increased as age in the RPL group in the range of 31 to 35 years, after which a decrease in frequency was observed. Two other meta-analyses also reported [9,10] that the mean age with positive TAI in women with RPL was slightly higher than women with negative TAI. In this study, there was no statistically significant difference in the mean age in women with positive and negative TAI.…”
Section: Discussionmentioning
confidence: 88%
“…Some of these studies have shown that serum thyrotropin (TSH) levels among women with a history of recurrent miscarriage and TAI are within normal parameters, but higher than those without TAI [9]. Additionally, two systematic reviews reported that in women who had a miscarriage, the average age of women with TAI was slightly higher than without TAI [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported in the literature that thyroid disorders during pregnancy are associated with severe maternal, fetal and neonatal complications such as miscarriage (20), preterm delivery (21) and preeclampsia (22).…”
Section: Literature Review the Fetal Thyroid And The Role Of Ths In Cmentioning
confidence: 99%
“…Е-mail: dr.yevstratieva@gmail.com нями ЩЗ можуть діагностувати порушення менструальної функції у формі олігоопсоменореї чи гіперполіменореї, рідше -аменореї. Рання діагностика та лікування ПМЦ забезпечує максимальну компенсацію нейроендокринних порушень, знижує частоту ускладнень, підвищує ефективність профілактики порушень репродуктивної функції у дітородному віці та, як наслідок, сприяє зменшенню репродуктивних втрат [4]. Отже, проблема безпліддя на тлі дисфункції ЩЗ потребує подальшого вивчення для розробки чіткіших практичних рекомендацій щодо діагностики та лікування цього захворювання.…”
Section: тернопільський національний медичний університет імені і яunclassified
“…Порушення репродуктивної системи відрізняються залежно від форми патології ЩЗ [4]. При порушеннях менструальної функції на тлі йододефіцитних станів відзначено зниження функції ЩЗ, що супроводжується дисфункцією гіпоталамо-гіпофізарно-яєчникової системи у цілому [3].…”
unclassified